A Compact Multi-Band MIMO Antenna with High Isolation for C and X Bands Using Defected Ground Structure - Pouyanfar, Negin; Ghobadi, Changiz; Nourinia, Javad; Pedram, Kioumars; Majidzadeh, Maryam (Společnost pro radioelektronické inženýrství, 2018)
A compact multi-band multi-input multi-output (MIMO) antenna with high isolation is proposed for C and X bands applications. The antenna consists of two trapezoidal-shaped patches printed on FR-4 substrate with a thickness of 1.6 mm and compact size of 17 mm×42 mm. Defected ground structure (DGS) is wisely embedded in antenna body to reduce the mutual coupling between the antenna elements. This modification suitably enhances the isolation by 30dB in C-band extended from 6.6 GHz to 7.6 GHz and by 17 dB in X-band between 8.3 GHz to 10 GHz. Moreover, five meander line rectangular patches are properly included to further improve the mutual coupling and eliminate the antenna size increment, simultaneously. The aforementioned meander lines also improve impedance bandwidth of the antenna as well as impedance matching over the entire frequency band. Close agreement of simulated and measured results confirm the antenna outperformance. Design, simulation, and performance analysis of the proposed antenna is discussed in detail.
Keywords: Multi-Input Multi-Output; Defected Ground Structure (DGS); mutual coupling; C band; X band